2015
DOI: 10.1111/bjh.13607
|View full text |Cite
|
Sign up to set email alerts
|

Tamibarotene in patients with acute promyelocytic leukaemia relapsing after treatment with all‐trans retinoic acid and arsenic trioxide

Abstract: Summary Treatment of acute promyelocytic leukaemia (APL) with arsenic trioxide (ATO) and all-trans retinoic acid (ATRA) is highly effective first-line therapy, although approximately 5–10% of patients relapse. Tamibarotene is a synthetic retinoid with activity in APL patients who relapse after chemotherapy and ATRA, but has not been studied in relapse after treatment with ATO and ATRA. We report on a phase II study of tamibarotene in adult patients with relapsed or refractory APL after treatment with ATRA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 15 publications
1
20
0
Order By: Relevance
“…Tamibarotene (formerly called Am80), a synthetic retinoic acid with more potent in vitro activity than ATRA, has demonstrated a favorable pharmacokinetic profile, as the plasma level does not decline after daily administration [259]. It produced interesting results when used as a single agent for induction in relapsed/refractory patients who previously received ATRA and ATO [260]. In a study reported by the Japan Adult Leukaemia Study Group, tamibarotene led to an improvement in relapse-free survival (RFS) when used as a maintenance therapy in high-risk APL [110].…”
Section: Discussionmentioning
confidence: 99%
“…Tamibarotene (formerly called Am80), a synthetic retinoic acid with more potent in vitro activity than ATRA, has demonstrated a favorable pharmacokinetic profile, as the plasma level does not decline after daily administration [259]. It produced interesting results when used as a single agent for induction in relapsed/refractory patients who previously received ATRA and ATO [260]. In a study reported by the Japan Adult Leukaemia Study Group, tamibarotene led to an improvement in relapse-free survival (RFS) when used as a maintenance therapy in high-risk APL [110].…”
Section: Discussionmentioning
confidence: 99%
“…Tamibarotene, a synthetic retinoid drug, can overcome ATRA resistance and appears promising in relapsed/refractory APL patients (Sanford et al , ). Furthermore, oral ATO is effective in relapsed children where home‐based therapy is desirable (Au et al , ).…”
Section: Future Perspectivesmentioning
confidence: 99%
“…Overall response rate was 64% with 21% mCR. Relapses were frequent after a median of 4·6 months (Sanford et al , ). These data suggest activity efficacy of tamibarotene in advanced disease; its use in association with ATO will probably be explored in the near future.…”
Section: Current New Therapeutic Strategiesmentioning
confidence: 99%